THE POPULARITY OF KOREAN MUSIC (K-POP) AMONG PERANAKAN CmNESE UNDERGRADUATE STUDENTS OF SOEGIJAPRANATA CATHOLIC UNIVERSITY - Ekawati Marhaenny Dukut; Shierly June (Soegijapranata Catholic University, 2012)
Korean Wave is one of the popular cultures that has developed in Indonesia. It comes with some special products that attract Indonesian youth. Doing a research on this, it is found that Korean music or K-Pop has noticeable popularity among 96.87% of selected peranakan Chinese undergraduate students in Soegijapranata Catholic University. This article to discusses and analyzes the phenomenon and the development of K-Pop of the factors of why the peranakan Chinese undergraduate students in Soegijapranata Catholic University are found of the Korean Wave product.